Inkjet-printed iontronics for human-machine interface applications - Gao, Dace (Nanyang Technological University, 2021)
This PhD study aims at developing soft human-machine interfaces (HMIs) based on the emerging iontronic technology. It involves the preparation of new materials, the development of advanced manufacturing protocols, and the fabrication of iontronic devises with unprecedented modalities. Next generation HMIs are expected to be lightweight and intrinsically soft for better human-machine or machine-environment interaction. The realization of these novel characteristics depends on the availability of soft materials, typically soft conductors. In contrast with the strategies depending on stretchable electronic conductors, the usage of gel-like ionic conductors represents an entirely different approach which has intrigued intense research interests in recent years. To promote this field, ionic conductors need to be patterned into desired shapes to serve as functional electrodes. After exploring various manufacturing techniques, inkjet printing is chosen for this study as it can provide micrometer-scale patterning resolution, and the direct ink writing (DIW) method eliminates the usage of any mold or mask which may potentially contaminate or destruct the already printed ionic gels on the elastomeric substrate. Interactive HMIs are bidirectional systems containing both receptive and responsive modules. Applications including capacitive touch sensing, electrostatic actuation, and electrostatic adhesion are of our interests in this thesis. We start with the receptive part and fabricate an iontronic touch sensing matrix which is transparent, stretchable, and strain-insensitive. Responsive iontronic interface is then demonstrated by a seamless integration of iontronic actuator and adhesive patch. Iontronic adhesion represents a novel mechanism wherein the rapid relaxation of spatial charges at the electronic/ionic interface is exploited to modulate electromechanical transduction in a responsive iontronic device.